2020
DOI: 10.1186/s13613-020-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of CRRT: a pathway to optimize therapy

Abstract: Severe acute kidney injury (AKI), especially when caused or accompanied by sepsis, is associated with prolonged hospitalization, progression to chronic kidney disease (CKD), financial burden, and high mortality rate. Continuous renal replacement therapy (CRRT) is a predominant form of renal replacement therapy (RRT) in the intensive care unit (ICU) due to its accurate volume control, steady acid-base and electrolyte correction, and achievement of hemodynamic stability. This manuscript reviews the different asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
111
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 98 publications
0
111
0
3
Order By: Relevance
“…Hemoadsorption with CytoSorb can be used predominantly in patients suffering from septic shock with careful decision-making, according to the APACHE II score. The basic principle of these blood purification devices, using more effective membranes or columns incorporated in CRRT, is removal of pro-inflammatory cytokines (e.g., IL-6, IL-8, TNFα) and endotoxins to stabilize the patient’s hemodynamics and decrease the need for vasopressor therapy [ 87 ]. Preserving adequate fluid balance, net ultrafiltration, treatment dose, nutritional support and antibiotic treatment are a vital component of the therapeutic approach in critically ill septic patients [ 88 ].…”
Section: Therapeutic Approaches In Septic Patients With Akimentioning
confidence: 99%
“…Hemoadsorption with CytoSorb can be used predominantly in patients suffering from septic shock with careful decision-making, according to the APACHE II score. The basic principle of these blood purification devices, using more effective membranes or columns incorporated in CRRT, is removal of pro-inflammatory cytokines (e.g., IL-6, IL-8, TNFα) and endotoxins to stabilize the patient’s hemodynamics and decrease the need for vasopressor therapy [ 87 ]. Preserving adequate fluid balance, net ultrafiltration, treatment dose, nutritional support and antibiotic treatment are a vital component of the therapeutic approach in critically ill septic patients [ 88 ].…”
Section: Therapeutic Approaches In Septic Patients With Akimentioning
confidence: 99%
“…14,16 However, the benefits of CRRT are still no consistent conclusion in critically ill patients. 17 CRRT significantly reduced the level of IL-6 and decreases hospital mortality rate in pediatric severe sepsis, especially in patients with acute respiratory distress syndrome (ARDS). 18 Besides, a meta-analysis revealed that patients who received CRRT had significantly lower mortality compared to conventional therapy.…”
mentioning
confidence: 99%
“…16 The relationship between CRRT and patients' outcome varied in patients with the different disease and was effected by the modalities, anticoagulation, vascular access management, timing of initiation and intensity of CRRT. 17,20,21 To date, no specific treatment has been confirmed to be effective for COVID-19, and supportive treatment remains essential. As far as we know, the effect of CRRT on critically ill patients with COVID-19 has not been reported.…”
mentioning
confidence: 99%
“…Nowadays, renal replacement therapy (RRT) has been one of the most crucial life supports in ICU so that the incidence of AKI treated with RRT is increasing steeply [3,4]. RRT is regarded as lifesustaining for AKI, with signi cant value in critically ill [5][6][7]. There is no doubt that the decision whether or not to choose RRT should be described as preference-sensitive.…”
Section: Introductionmentioning
confidence: 99%